A Study to Evaluate the Effect of Some Water Quality Parameters on the Decay of Free Residual Chlorine in the Drinking Water Supply Network in Latakia City using Python Regression Models - مي الفريد ناصر; رائد جعفر; هيثم جناد; عادل عوض (Latakia University Journal -Engineering Sciences Series, 2023)
This study aimed to evaluate the effect of some water quality parameters on the decay of free residual chlorine in the drinking water supply network in Latakia , Five sampling points were selected on the main network that feeds the Latakia city, starting from the treatment plant (Al-Sin) to Al-Montazah tank (Latakia) , These Samples were collected once a month , The study has lasted for seven months , from June (2021) to December (2021) , the measurement interval was determined and free residual chlorine concentration , temperature and pH were measured at the site while (turbidity - phosphates - nitrates - dissolved solids - electrical conductivity - sodium chloride) in the laboratory.The Python language was used to determine the correlation coefficient of the free residual chlorine with the studied parameters, which the correlation was inversely negative .Two models were built , Multiple linear regression and multivariate adaptive regression to determine the percentage of variance in free residual chlorine that is explained by the studied parameters and to evaluate the accuracy of the models.The variance was (86%) and this (86%) of the decrease in chlorine was related to the regression equation factors and that (14%) was due to other factors, the (R-squared) value for the first and second models, respectively, was (R2 = 0.81, R2 = 0.86) and (MSE = 0.008, MSE = 0.0046) thus based on the higher (R2) value (R2 = 0.86), the best and most suitable model for the data is multivariate adaptive regression .